FACTS controllers in power transmission and distribution - Padiyar, K. R. (New Age International, 2007)
About the Book: The emerging technology of Flexible AC Transmission System (FACTS) enables planning and operation of power systems at minimum costs, without compromising security. This is based on modern high power electronic systems that provide fast controllability to ensure 'flexible' operation under changing system conditions. This book presents a comprehensive treatment of the subject by discussing the operating principles, mathematical models, control design and issues that affect the applications. The concepts are explained often with illustrative examples and case studies. In particul.